Melittin as a therapeutic agent for rheumatoid arthritis: mechanistic insights, advanced delivery systems, and future perspectives - Pareek, Ashutosh; Mehlawat, Khushbu; Tripathi, Kritika; Pareek, Aaushi; Chaudhary, Simran; Ratan, Yashumati; Apostolopoulos, Vasso; Chuturgoon, Anil (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA), a condition characterized by joint deterioration through the action of matrix metalloproteinases (MMPs), is prevalent worldwide. Bee venom (BV) has traditionally been used in Chinese medicine for pain, arthritis, rheumatism, skin diseases, etc. BV is enriched with active substances, notably melittin and phospholipase A2 (PLA2), offering significant therapeutic potential. Hence, the review summarizes current insights into BV’s composition, antiarthritic mechanism and pharmacological benefits, focusing on melittin. Constituting 50-60% of BV, melittin notably downregulates nuclear factor Kappa B (NF-κB) activity, inhibits MMP-1 and MMP-8, and diminishes tumor necrosis factor (TNF-α), all of which contribute to the mitigation of type 2 collagen degradation. Despite its potential, melittin exhibits hemolytic activity and can significantly affect cell membranes, limiting its application, which poses a challenge to its therapeutic use. To overcome these challenges, delivery techniques utilizing nanocarriers and modifications in amino acid sequencing have been developed. Recent advancements in delivery systems, including nanocarriers, transdermal patches, and nanoemulsions, aim to minimize toxicity, expanding its therapeutic utility for RA. This article explores these novel strategies, underlining the evolving role of melittin in RA management.